2007
DOI: 10.4314/sajas.v37i3.4086
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Effects of short chain fatty acid (SCFA) supplementation on performance and egg characteristics of old breeder hens

Abstract: A study was conducted to determine the effect of supplementing the diet of breeder hens with a shortchain fatty acid (SCFA) premix, containing 509 g fatty acid salts/kg of which 285 g were calcium butyrate, on their eggshell characteristics and the hatching percentage of the eggs. One thousand six hundred 66-week old White Bovans laying breeder hens were used in this experiment. They were housed in eight identical pens, each containing 200 birds, and four pens were used per treatment. The SCFA premix was inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…The results of the present study are similar to those reported by Sengor et al (2007), who in an experiment with old breeder White Bovans hens found that eggshell breaking strength was increased after the inclusion of short-chain fatty acids (VFA) in the diet. The authors also reported that VFA decreased the number of dirty, cracked and misshapen eggs.…”
Section: Eggshell Qualitysupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the present study are similar to those reported by Sengor et al (2007), who in an experiment with old breeder White Bovans hens found that eggshell breaking strength was increased after the inclusion of short-chain fatty acids (VFA) in the diet. The authors also reported that VFA decreased the number of dirty, cracked and misshapen eggs.…”
Section: Eggshell Qualitysupporting
confidence: 91%
“…One of the factors the mechanism of this effect is connected with is the reduction of intestinal pH, which leads to an increase in the activity of digestive enzymes (accelerated conversion of pepsinogen to pepsin) and in the solubility of minerals. Some experiments with layers and old broiler breeder hens have demonstrated that organic acids can have a positive effect on laying performance and eggshell quality (Park et al, 2002;Yesilbag and Colpan, 2006;Sengor et al, 2007;Soltan, 2008). In the recent study with older laying hens (from 75 to 80 weeks of age) organic acids beneficially affected soft-shell + broken egg production, feed conversion ratio and IgY concentration in yolks, but had no influence on laying rate and eggshell strength and thickness (Park et al, 2009).…”
mentioning
confidence: 99%
“…But, the author observed increased egg shell strength. Butyrate (addition level of 185 mg/kg) can enhance the egg shell strength in old hens and decrease the number of misshapen eggs ( Sengor et al., 2007 ), which is similar to our study in which the egg breaking rate tended to decrease with monobutyrin supplementation.…”
Section: Resultssupporting
confidence: 88%
“…Positive effects of organic acids on egg production, eggshell quality and mineral absorption have been determined by some researchers (Yesilbag and Colpan, 2006;Sengor et al, 2007;Sarı and Kaya, 2017). Soltan (2008) reported that supplementation of a commercial organic acid blend "ProviMax" containing calcium butyrate, calcium propionate, calcium lactate and fumaric acid improved eggshell thickness and serum Ca level.…”
Section: Effect Of Feed Additives On Mineral Absorption and Bone Charmentioning
confidence: 97%